Wydatki samorządów terytorialnych w krajach Unii Europejskiej - Markowska-Bzducha, Ewa (Capital Expenditures of Local Governments in the European Union, 2006)
The aim of the following study is to analyze the level of capital expenditures of local governments in 25 countries of the EU. There is no homogenous European model for local governments. Autonomous structures are quite diversed in researched countries. Every country differs in the degree of the decentralization of assignments and public finances as well. However, there are some common features for all local authorities, especially in the range of their main competences. Rates showing the level of local governments' expenses in relation to GDP are differential, but there is no noticeable difference as far as former and new members of the UE are concerned. Local governments of 10 ascending countries take great investment effort appropriating major part of their resources for development purposes; but in absolute values there are great differences for old members' favour which are caused by much higher level of GDP.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 560-568